New challenges for the People’s Republic of China foreign policy - Baichorov, Aleksandr M. (Journal of the Belarusian State University. International Relations, 2023)
The article provides an overview of the challenges the People’s Republic of China faces and its responses to them. Main attention is drawn to the new challenges that mostly appeared at the end of the second decade of the 21st century. These challenges associated with the slowing down of the economic development of China, the Western policy of containment towards the country and the consequences of the Covid-19 pandemic. It is determined that the pace of the China’s economic growth might never return to the double digits because of the combined effect of accumulated internal structural and financial problems and pressure from the West. The Western containment strategy includes not just direct tariffs and limitations against the Chinese goods, services and investments but such changes in the world economy that will make more difficult for China to compete in the world markets. The anti-Covid policy of the Chinese government delivered a striking blow to the country’s export and contributed to the slowing down of the national economy. The article strives to prove a hypothesis that the PRC’s government managed to modify its foreign policy strategy to meet the traditional and new challenges and provide the best possible external conditions for the great rejuvenation of the Chinese nation.